Comparative analisis of the dynamics of glycemia using continuos glucose monitoring during on-pump or off-pump coronary artery bypass grafting - Elena Zelikovna Golukhova (Endocrinology Research Centre, 2016)
Objective.Using continuous glucose monitoring to determine diagnostic optimisation of metabolic status and perioperative management techniques in coronary heart disease and diabetes mellitus type 2 (DMT2) in order to reduce the risk of perioperative complications.Materials and Methods.We examined 80 patients with ischaemic heart disease, aged 39 to 71 years. Patients were divided into four groups. Separation criteria were the presence of diabetes and the method of myocardial revascularisation. For all patients in the intra- and early postoperative periods the continuous glucose monitoring was performed by CGM System Gold MMT-7102W (Medtronic, USA); also blood glucose level has been controlled by sample testing of venous blood (laboratory glucose oxidase electrochemical method) and capillary blood by portable blood glucose meter (OneTouch Ultra, LifeScan, USA).Results.In our study, average blood glucose levels from the results of measurements with CGMS at different operative stages and in the early postoperative period in four groups of patients were measured. Glucose level monitoring in diabetic patients during coronary revascularisation demonstrated that perioperative hyperglycaemia in patients with coronary artery disease who underwent cardiopulmonary bypass was observed regardless of whether they had metabolic carbohydrate disorders during the preoperative period. The most significant changes in glucose were observed in these patients at the stage of cardiopulmonary bypass, while in patients with T2DM, the glycaemic response to intervention (even with satisfactory preoperative compensation of carbohydrate metabolism) was more intense and less manageable than that in surgical patients without diabetes. When operating on a beating heart, intraoperative hyperglycaemia was observed more frequently in patients with T2DM than in controls at the stage of bypass, but glucose indicators were significantly lower than in groups of patients with T2DM who underwent cardiopulmonary bypass.Conclusion.Given the lack of significant differences between the laboratory glucose rates, data from CGM System Gold and OneTouch Ultra demonstrated that continuous glucose monitoring can reliably assess the presence or absence of metabolic changes in the perioperative period and thus reduce the likelihood of complications.